2008
DOI: 10.1007/s10863-008-9154-x
|View full text |Cite
|
Sign up to set email alerts
|

Low resolution structure of subunit b (b 22–156) of Escherichia coli F1FO ATP synthase in solution and the b−δ assembly

Abstract: The first low resolution solution structure of the soluble domain of subunit b (b (22-156)) of the Escherichia coli F(1)F(O) ATPsynthase was determined from small-angle X-ray scattering data. The dimeric protein has a boomerang-like shape with a total length of 16.2 +/- 0.3 nm. Fluorescence correlation spectroscopy (FCS) shows that the protein binds effectively to the subunit delta, confirming their described neighborhood. Using the recombinant C-terminal domain (delta(91-177)) of subunit delta and the C-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The crystallographic structure of the major part of the dimerization domain, b62-122, revealed an ␣-helix with a length of 9.0 nm (12). Most recently, the NMR solution structure of the very C-terminal segment, b140-156, which interacts with the C terminus of subunit ␦ (␦91-177), has been determined by NMR spectroscopy (26). This molecule adopts a stable helix formation in solution with a flexible tail between amino acid residues 140 and 145.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The crystallographic structure of the major part of the dimerization domain, b62-122, revealed an ␣-helix with a length of 9.0 nm (12). Most recently, the NMR solution structure of the very C-terminal segment, b140-156, which interacts with the C terminus of subunit ␦ (␦91-177), has been determined by NMR spectroscopy (26). This molecule adopts a stable helix formation in solution with a flexible tail between amino acid residues 140 and 145.…”
mentioning
confidence: 99%
“…This molecule adopts a stable helix formation in solution with a flexible tail between amino acid residues 140 and 145. SAXS (26) and analytical ultracentrifuge studies have indicated that the soluble domain of subunit b (b21-156, b22-156) is dimeric in solution (12). So far, no high-resolution structure of the tether domain, including residues 25 to 52, or the N-terminal segment of the dimerization domain, which is formed by residues 53 to 122, is available (14).…”
mentioning
confidence: 99%
“…It is mainly located in the unstacked regions of thylakoid membranes. The chloroplast ATP synthase consists of two parts, the hydrophilic CF 1 (subunit  3 ,  3 , ,  and ) and the membrane integrated CF o (subunits I, II, III 14 and IV). The CF 1 contains the nucleotide binding, catalytic and regulatory sites of ATP complex.…”
mentioning
confidence: 99%
“…The CF o is involved in the proton transport through thylakoids [1]. These two parts are connected by a central stalk consisting of subunits , , III 14 and a peripheral stalk composed of subunits I, II and  [2]. The proton movement through subunit III complex drives the rotation of subunits  and  in catalytic core of  3  3 hexamer to catalyze ATP synthesis [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation